Rational synthesis of modulated in2O3 based nanowires - Zhu, Yuxuan (2012)
Indium tin oxide (ITO) is a multifunctional semiconductor material widely used for transparent conducting oxides (TCO) in nanotechnology. A systematical research on the vapor transport growth of ITO nanowires and comprehensive study on characterizations of physical properties of nanowires are presented. Main topics in this thesis cover the controlling of synthesis parameters in ITO nanowires synthesis, structure characterization by XRD and electrical properties measurement of ITO nanowire. By comparing the measured resistivity of nanowire with the reference value, ITO nanowires showed remarkable electrical conductivity property.